BENTUK KERJASAMA SISWA KELAS XI IIS DALAM PEMBELAJARAN SOSIOLOGI SMA DARUT TAUHID SUNGAI RAYA - Ivan Kamaruzzaman; Yohanes Bahari; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the forms of students’ cooperation in sociology instruction at SMA Darut Tauhid Sungai Raya. The method used in this study was descriptive with a qualitative approach. The data were collected using observation, interviews, and documentary study techniques. The analysis was presented descriptively by involving five informants, which comprised one teacher of a sociology subject and four students of class XI. The findings showed that the forms of the cooperation were seen when a student spontaneously lent his or her book to another who did not bring theirs, explained the material that was not understood by classmates, and reprimanded his or her classmates when they ate or slept during the class. As direct cooperation in class, the teacher instructed the students to form a group discussion and thus created interaction and cooperation between the members. The form of traditional cooperation was seen from mutual help in resolving the difficulties working on assignment. This is cooperation, students can give each other explanations for materials that are not understood by their classmates.  Keywords :  Cooperation, Students, Sociology Instructions.